Extensive full thickness abdominal wall reconstruction using anterolateral thigh compound flap modifications. Issue 3 (18th October 2019) - Oh, Jeongseok; Oh, Joon Seok; Eun, Seok‐Chan
Abstract: Purpose: Abdominal wall reconstruction is challenging, which demands adequate skin coverage and structural support. The anterolateral thigh (ALT) flap including fascial portion can be useful in such cases. Methods: Retrospective chart review of five patients that underwent complex abdominal wall defects reconstruction with ALT free flaps with fascia lata was conducted. Patient age ranged from 49 to 69 years (average: 57.4). The etiology of defects was infected liposuction site, small bowel perforation, esophageal cancer, diverticulum perforation, and Hartmann operation. The average size of the defect was 17.4 × 10 cm (9 × 9 21 × 18). Single‐stage reconstruction using ALT flaps based on the lateral circumflex femoral artery was done in all patients. Exposed intestines were successfully covered and reinforced utilizing fascial component. Results: The average size of the flap was 17.4 × 8 cm (9 × 9 cm 25 × 10 cm). One partial flap necrosis, venous congestion, and infection occurred. These complications were treated successfully. During the follow‐up (12–96 months, mean: 63), all patients achieved functional stabilization and returned to normal activities. Conclusion: ALT flap combined with its fascial component is useful for abdominal wall. It can be a reliable option in cases of intestinal exposure.